Vegetation Density of Green Open Spaces as a Key Determinant of Outdoor Thermal Comfort on the Universitas Palangka Raya Campus: Kerapatan Vegetasi Ruang Terbuka Hijau sebagai Penentu Kenyamanan Termal Luar Ruangan di Kampus Universitas Palangka Raya - Nuswantoro, Waluyo; Ludang, Yetrie; Sutrisno, Herwin; Uda, Subrata Aditama Kittie Aidon (Media Ilmiah Teknik Lingkungan (MITL), 2026)
Outdoor thermal comfort plays a crucial role in supporting daily academic activities, particularly in humid tropical regions characterized by high air temperature and relative humidity. Air temperature and relative humidity were measured at 30 observation points representing different land-cover conditions across the campus area. Outdoor thermal comfort was evaluated using the Thermal Humidity Index (THI), while vegetation density was assessed using the Normalized Difference Vegetation Index (NDVI) derived from Landsat 8 imagery. Statistical analysis was applied to examine the relationship between NDVI and THI. The results indicate a consistent negative relationship between vegetation density and THI. Areas with higher NDVI values tend to exhibit lower THI levels, reflecting more comfortable thermal conditions. In contrast, locations dominated by built-up surfaces and sparse vegetation show higher THI values and experience greater thermal discomfort, particularly during daytime periods. Although the overall proportion of green open space on the campus meets regulatory requirements, the spatial distribution and density of vegetation vary considerably across activity zones. These findings highlight that vegetation density is a key factor in improving outdoor thermal comfort in tropical university campuses. Strategic enhancement of vegetation density, especially in high-activity areas, is essential to support a more thermally comfortable and sustainable campus environment.